Evaluation of the quality of health applications using the System Usability Scale - Afrizal, Sandra; Prihatni, Rima; Priyo Hastono, Sutanto (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
Current technological developments have made it easier for the public to access online healthcare services. One such online healthcare provider is Halodoc. The application has been downloaded by millions of people in Indonesia. Therefore, the purpose of this study was to evaluate the quality of Halodoc, a healthcare application, using the System Usability Scale (SUS) method. This research method utilized a survey distributed via Google Forms containing ten questions about users' experiences using the Halodoc healthcare application. The results showed that the average SUS score was 78.8, categorized as good. The study concluded that the Halodoc application had a fairly good level of acceptance, was easy to use, and respondents who had previously used the application understood its benefits. Several suggestions were provided for the development of this application, including the addition of a personal medical record feature, additional payment methods, and an emergency feature.